Performance Analysis of Binary Exponential Backoff and Improved Backoff for WPAN. (18th January 2010) - Mehta, S.; Kwak, K. S.
Abstract : The IEEE 802.15.3 medium access control (MAC) is proposed, especially, for wireless personal area network (WPAN) short and high data rates applications, to coordinate the access to the wireless medium among the competing devices. A concept of a geometrically increasing probability distribution for contention process was brought up in the work of Tay et al. (2004). In this paper, we adopt this idea as improved backoff (IB) for contention process of IEEE 802.15.3, where binary exponential backoff (BEB) is originally used. Here, we propose an analytical model for IB and compared both BEB and IB for saturated and nonsaturated traffic conditions. Furthermore, our research results demonstrate that IB provides an edge over BEB in terms of channel efficiency, channel access delay, and energy efficiency.